Pengaruh Kinerja Amc Dalam Pengawasan Fod Terhadap Keselamatan Penerbangan di Bandar Udara Internasional Sentani - Angelin Cindy Clara Manga’pan; Kifni Yudianto (Jurnal Bisnis Inovatif dan Digital, 2024)
Increased activity in the airside area, especially on the apron, causes the emergence of foreign objects such as gravel and oil spills that can disrupt flight safety. Apron Movement Control (AMC) plays a crucial role in regulating aircraft traffic, monitoring the apron area, and maintaining cleanliness from Foreign Object Debris (FOD). This study aims to evaluate the effect of AMC performance in FOD supervision on flight safety at Sentani International Airport. The method used is a quantitative approach with a saturated sampling technique, involving airside officers from airlines, Ground Handling (GH), Ground Support Equipment (GSE), and Marshallers. Data were collected through a closed questionnaire with a 4-point Likert scale and analyzed using validity, reliability, simple linear regression, T-test, and coefficient of determination. The results of the analysis show that AMC performance has a positive and significant effect on flight safety, with a significance value of the T test <0.05. The coefficient of determination (R²) of 0.916 indicates that AMC contributes 91.6% to flight safety, while the rest is influenced by other factors. This finding emphasizes the importance of improving the professionalism and effectiveness of AMC officers' performance.